Two scenes: Spaniards and Englishmen arrive in America (Journal of Parents and Teachers, 2026)
The author proposes a particular way of presenting and teaching an important historical topic – that of the Americas – given that children and young people will learn what their parents and teachers teach them and, above all, the attitudes they perceive in them. Therefore, to examine the reasons why the Spanish and English set out on the voyage that led to the Discovery, two scenes suggested in the journal *Social Education* have been selected; these are used in US schools to teach this event.
Keywords: Discovery of the Americas; New World; Spaniards; English